Penggunaan Algoritma Kriptografi Steganografi Least Significant Bit Untuk Pengamanan Pesan Teks dan Data Video - Gunawan, Indra (STIKOM Tunas Bangsa Pematangsiantar, 2018)
Some areas that are still discussed from a computer science research for a data security is the use of LSB steganography (Least Significant Bit) cryptography algorithm. Delivery of text and video data without being equipped with a security system from the LSB steganography algorithm can eliminate messages to be inserted into the video. The use of the LSB steganography algorithm can improve the security of messages to be sliced and sent to the recipients of messages. This analysis aims to improve text and video security by inserting text into video, then shuffling video so that the video can not be seen.